Faktor Sosial dan Faktor Pribadi Terhadap Keputusan Menggunakan Jasa KSU Surya Muhammadiyah - Muhamad Subhan; Sissah; Richa Luthfiatun Nisa Octaviandini (STEKOM PRESS, 2023)
The existence of organizations such as Islamic financial institutions that help improve the welfare of society according to their function, namely saving money and providing loan assistance for business capital and comsumtions. There are various types of LKM, one of which is cooperatives. This study aims to determine the..influence of social factors and./personal factors on people’s decisions to use the services of KSU Surya Muhammadiyah, either partially or simultaneously. This Study used a quantitative method using 50 samples taken by purposive sampling method from the KSU Surya Muhammadiyah customer population. Data collection technique were interviews, observation, questionnaires, and documentations. Then, the questionnaires were tested with validity and reliability tests to ensure the accuracy of the questionnaires. Furthermore, classical asumption tests and hypothesis tests were carried out including multiple,,linearregression tests, the coefficient of determination (R2), t-tes, .and F-test. The results of this study are as.follows: (1) social factors have effect on people’s decitions to use services of KSU Surya Muhammadiyah, with a t .count of 2,254 while .t table of 2,012 or t count < t table..and a significance level of 0,026 > 0,05. (2) personal factors influence people’s decitions to use the services of KSU Surya Muhammadiyah, with a t count of 3,093 while t table is 2,012 or tcount > t table and asignificance level of 0,003 < 0,05. (3) social and personal factors simultaneously influence the community’s decition to use the services of KSU Surya Muhammadiyah. Where the sigvalue is 0,000 < 0,005 and F count is 79,385 > F table 3,20. It can be concluded fromthe test results, namely: (1) H1 is accepted,,and H0 is rejected, (2) H2 is a accepted and H0 isrejected, (3) H3 is accepted and H0 is rejected. If the number of customers decreases, it is necessary topay attention tothese factors anything that can influence customer interest in choosing at KSU Surya Muhammadiyah Pematang Kolim Village